2020
DOI: 10.3390/met10030298
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Multi-Pass Friction Stir Processing on Microstructures and Mechanical Properties of the 1060Al/Q235 Composite Plate

Abstract: Steel cuttings, holes and cracks always exist at the interfaces in the composite plate. Multi-pass friction stir processing (M-FSP) is proposed in this research to optimize the interface microstructure and the interface connection for the 1060Al/Q235 composite plate. Results show that the microstructures of 1060Al after M-FSP are fine and uniform owing to the strong stirring effect and recrystallization. Micro-defects formed by the welding can be repaired by the M-FSP. However, tunnel defects can also be forme… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Fine and ultra-fine grains bear the maximum tensile load before fracture. A better interfacial bonding assists in the transfer of load to intermetallic particles [48][49][50]. A previous study reported that increased Cu content enhanced the UTS from 192 MPa (0wt%Cu) to 280 MPa (15wt%Cu) at the stirred zone.…”
Section: Friction Stir Processingmentioning
confidence: 98%
“…Fine and ultra-fine grains bear the maximum tensile load before fracture. A better interfacial bonding assists in the transfer of load to intermetallic particles [48][49][50]. A previous study reported that increased Cu content enhanced the UTS from 192 MPa (0wt%Cu) to 280 MPa (15wt%Cu) at the stirred zone.…”
Section: Friction Stir Processingmentioning
confidence: 98%
“…If the asymmetry in the temperature distribution and material flow in the FSW process can be eliminated and the process turns into a relatively symmetrical process, the mechanical quality of the joint can be improved [29][30][31]. Different solutions have been suggested to eliminate this disadvantage, which includes the use of Reverse Dual-Rotation Friction Stir Welding (RDR-FSW) [32,33], implementation of the FSW process using tandem tools, using Multi-Pass Friction Welding (MP-FSW) [34][35][36] with reverse rotation of the tool and the use of Parallel-Friction Stir Welding (P-FSW) [37].…”
Section: Introductionmentioning
confidence: 99%